Quantitative Analysis of Explanatory Factors Disclosures in Hedge Fund - Zhou, Zhanxu (2010)
In this paper, we carry out a series of quantitative analysis with an aim to provide a deeper insight about the adjusted excess returns of hedge fund indices and the potential risk factors that influence the strategies. In order to explore what potential explanatory factors involved in hedge fund, we extract eight hedge fund style indices from each of two famous database during the period from January 2001 to June 2010, and select typical potential risk factors which included common market index factors, Primitive trend-following (PTF) factors based on look back straddle, Fama-French and Carhart factors, commodity factor, Credit spread and additional trading strategy factors. Stepwise regressions will be applied to extract dominate potential risk factors due to that researchers generally accepted that different hedge fund style indices may have different potential risk factor. In terms of the results of correlation and regression analysis, the relationship between hedge fund indices and potential risk factors will be finally made clear. As a result, these selected potential risk factors can explain a significant proportion of the excess returns on hedge fund indices.